A Liability and Insurance Regime for Space Debris Mitigation. Issue 1 (2nd January 2016) - Wang, Ting
ABSTRACT: Concerns about the threat that space debris pose to satellites are expected to increase as the number of mostly non-maneuverable microsatellites in low-Earth orbit grows. International guidelines developed to mitigate the risk from space debris are frequently not followed, however, and may not be able to cope with the dramatic growth expected in the number of satellites. Moreover, the current legal framework is unable to determine who is liable for losses in an on-orbital collision. A space surveillance data-sharing committee is proposed to solve this liability problem. Under the proposed liability rules, satellite operators would be liable for the debris they create and insurance companies would cover such a risk, creating a new financial incentive for operators to adopt space debris mitigation guidelines.